Linguistic Landscapes In Desa Kuta (e-Journal of Linguistics, 2019)
This research aimed to identify the presence of Linguistic Landscapes (LL) in DesaKuta. LL is sociolinguistic study of language used in outdoor signage that firstly introduce byLandry and Bourhis (1997). Desa Kuta as one of tourist destination in Bali experiences a greatdevelopment due to globalization effect. This great development can be seen clearly through thepresence of outdoor signs along the main roads of Desa Kuta. The research was conducted fromFebruary to March 2019. The finding showed there are 2.549 signs along the main roads of DesaKuta. The language used mostly in English with 1.332 signs (52%). As for the types, there are1.603 signs of commercial signs (65%). In term of the function, 2.320 signs (93%) areinformative.